2010
DOI: 10.4271/2010-01-0051
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Model for Low-Speed Bumper-to-Bumper Crashes

Abstract: The purpose of this study was to develop a numerical analytical model of collinear low-speed bumper-to-bumper crashes and use the model to perform parametric studies of low-speed crashes and to estimate the severity of low-speed crashes that have already occurred. The model treats the car body as a rigid structure and the bumper as a deformable structure attached to the vehicle. The theory used in the model is based on Newton's Laws. The model uses an Impact Force-Deformation (IF-D) function to determine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…Nonetheless, the analysis shows for the first time that linear acceleration time models applied to both the loading and unloading phases of low speed rear impact yield closed form solutions which provide a close match to the available experimental data. Furthermore, although (Scott et al, 2010) found from a parametric modeling study that the overall pulse duration is independent of impact speed for fixed restitution and stiffness, they also found significant variations in overall pulse duration when restitution and stiffness are varied. In this paper it has been shown for the first time that the time to common velocity (T cv ), as opposed to the overall pulse duration, is substantially independent of collision closing speed for a set of full-scale staged collisions, and that T cv can therefore be used as an explicit surrogate measure of the normalised vehicle stiffness.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Nonetheless, the analysis shows for the first time that linear acceleration time models applied to both the loading and unloading phases of low speed rear impact yield closed form solutions which provide a close match to the available experimental data. Furthermore, although (Scott et al, 2010) found from a parametric modeling study that the overall pulse duration is independent of impact speed for fixed restitution and stiffness, they also found significant variations in overall pulse duration when restitution and stiffness are varied. In this paper it has been shown for the first time that the time to common velocity (T cv ), as opposed to the overall pulse duration, is substantially independent of collision closing speed for a set of full-scale staged collisions, and that T cv can therefore be used as an explicit surrogate measure of the normalised vehicle stiffness.…”
Section: Discussionmentioning
confidence: 64%
“…The recent work by (Scott et al, 2010(Scott et al, , 2012Bonugli et al, 2014;Funk et al, 2014) has shown that, when experimental knowledge of the combined bumper deformation behavior is known for a specific vehicle pair, the impact response for a specific collision can be found. However, the tests they completed showed non-linear and variable bumper stiffnesses, and the approach yields nontrivial errors in the coefficient of restitution.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, a simulation model was developed to recreate low-speed bumper-to-bumper crashes where the only damage was to the bumpers (1). The impact force used in this simulation model is directly related to the force-deformation (F-D) characteristics of the bumpers involved in the crash being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The model is also used to compare that how the structural characteristics of the vehicles' bumpers and the closing speed affect the crash pulse and to demonstrate a technique to estimate the maximum severity of a low-speed crash that has already occurred [4].…”
Section: Literature Reviewmentioning
confidence: 99%